Composição corporal, perfil metabólico e inflamatório na heterozigose para uma mutação no gene do receptor do GHRH - Pereira, Rossana Maria Cahino (2007)
Different forms of isolated GH deficiency (IGHD) have an autosomal recessive mode of inheritance. The most common one (type IB) is often caused by bi-allelic mutations in the GHRH receptor (GHRHR) gene (GHRHR). Although heterozygous carriers of GHRHR mutations appear normal, the small size of most of the families and the fact that stature is a complex and polygenic trait prevented so far a careful analysis of their phenotype. To test the hypothesis that heterozygosity for a GHRHR mutation may be associated with a mild phenotype, we studied large Brazilian kindred with familial IGHD (Itabaianinha cohort). In this population, GHD is caused by a homozygous null mutation of the GHRHR. Adults and children with GHD have severe short stature, reduced lean mass, increased % fat mass, increased waist to hip (W/H) ratio, increased total and LDL-cholesterol and C-reactive protein (CRPus), increased systolic blood pressure, and increased insulin sensitivity. We studied 77 adult subjects (age 25-75) heterozygous for the mutation (WT/MT) and compared them with age and sex-matched controls homozygous for the wild-type allele (WT/WT) from the same population. Genotyping was performed by denaturing gradient gel electrophoresis from genomic DNA. We found no difference in adult height; blood pressure and standard deviation score for serum IGF-I between the two groups. Body weight, body mass index, skin folds, waist, hip, lean and fat mass were all reduced in WT/MT subjects. %FM and W/P ratio were similar in the two groups. Fasting insulin and in HOMAIR were lower in WT/M than in WT/WT. The other biochemical parameters (total and fractionated cholesterol, triglycerides, Lp (a), CRPus) were not different between the two groups. Our data shows that heterozygosity for a null GHRHR mutation is not associated with reduction in adult stature or reduction in serum IGF-I, but it causes a parallel decline in fat and lean mass, and an increase in insulin sensitivity. Heterozygosis for a null GHRHR mutation is not associated with reduction in adult stature or in serum IGF-I, but is causes changes in body composition and increase in HOMAIR. These effects do not seem to be modulated by changes circulating IGF-I.